Breaking Soybean Yield Barriers: A Cropping Systems Approach - I. A. Ciampitti; G. R. Balboa (Kansas Agricultural Experiment Station Research Reports, 2016)
During 2015, four soybean research trials were conducted in dryland and irrigated environments. Two trials were at Scandia, KS, and two were in Topeka, KS. The objective of these trials was to study the contribution of different farming systems to developing efficient and high-yielding soybean production systems. Each experiment had five treatments: common practices (CP), comprehensive fertilization (CF), production intensity (PI), ecological intensification (CF + PI), and advanced plus (AD). Under dryland and irrigation EI and AD treatments had the maximum yield in both locations. Under irrigation, yield gap was the largest as compared to the dryland environment in both locations. In all four experiments common practices had the lowest yield.
Keywords: soybean; yield gaps; cropping system